Analisis Peran Green Sukuk dalam Pembiayaan Sektor Renewable Energy di Indonesia untuk Mendukung Pencapaian Net Zero Emission - Aminin, Rista Izza; Khayati , Ismatul (Universitas Muhammadiyah Ponorogo, 2025)
Indonesia faces significant challenges in reducing carbon emissions from the energy sector while accelerating renewable energy development. To achieve the Net Zero Emission (NZE) target, innovative financing instruments are essential to mobilize large-scale sustainable investment. One such instrument is the Green Sukuk, which reflects the integration of Islamic finance and environmental objectives. This study aims to analyze the role of Green Sukuk in financing Indonesia’s renewable energy sector. Using a qualitative descriptive-analytical method, the research examines official documents and publications related to Green Sukuk during 2018–2023. The analysis focuses on issuance trends, mobilized funds, and their contribution to carbon emission reduction. The findings reveal that Green Sukuk mobilized USD 9.527 million and contributed to a reduction of 5,487,041 tons emissions in 2018–2022, equivalent to 0.46% of the 2030 NDC energy sector target. The findings affirm the strategic role of Green Sukuk as an effective Islamic finance instrument in advancing Indonesia’s clean energy transition. Nevertheless, its potential remains underutilized and requires further optimization through enhanced market literacy, strengthened institutional capacity, and broader outreach to investors and the wider public. Keywords: Green Sukuk, Renewable Energy, Net Zero Emission, Sharia Financing